Identification of differentially expressed genes of blood leukocytes for Schizophrenia - Wang, Feifan; Fan, Yao; Li, Yinghui; Zhou, Yuan; Wang, Xin; Zhu, Mengya; Chen, Xuefei; Xue, Yong; Shen, Chong (Frontiers in Genetics, 2024)
Background: Schizophrenia (SCZ) is a severe neurodevelopmental disorder with brain dysfunction. This study aimed to use bioinformatic analysis to identify candidate blood biomarkers for SCZ.The study collected peripheral blood leukocyte samples of 9 SCZ patients and 20 healthy controls for RNA sequencing analysis. Bioinformatic analyses included differential expression genes (DEGs) analysis, pathway enrichment analysis, and weighted gene coexpression network analysis (WGCNA).Results: This study identified 1205 statistically significant DEGs, of which 623 genes were upregulated and 582 genes were downregulated. Functional enrichment analysis showed that DEGs were mainly enriched in cell chemotaxis, cell surface, and serine peptidase activity, as well as involved in Natural killer cell-mediated cytotoxicity. WGCNA identified 16 gene coexpression modules, and 5 modules were significantly correlated with SCZ (P < 0.05). There were 106 upregulated genes and 90 downregulated genes in the 5 modules. The top ten genes sorted by the Degree algorithm were RPS28, BRD4, FUS, PABPC1, PCBP1, PCBP2, RPL27A, RPS21, RAG1, and RPL27. RAG1 and the other 9 genes belonged to the turquoise and pink module respectively. Pathway enrichment analysis indicated that these 10 genes were mainly involved in processes such as Ribosome, cytoplasmic translation, RNA binding, and protein binding.This study finds that the gene functions in key modules and related enrichment pathways may help to elucidate the molecular pathogenesis of SCZ, and the potential of key genes to become blood biomarkers for SCZ warrants further validation.